Medication adherence among hypertensive adults residing in a rural area of Dakshina Kannada district - Kumar, Ananta; R., Pracheth (International Journal Of Community Medicine And Public Health, 2018)
Background: Medication adherence is regarded as a critical determinant of control of hypertension. The objective of the study was to determine the prevalence and factors associated with medication adherence among hypertensive adults, residing in a rural area of Dakshina Kannada district. Methods: A cross-sectional study was conducted from August to November 2015. A pre-designed, pre-tested proforma was used to collect information. The study participants were enquired about the medication adherence using the Morisky medication adherence scale (MMAS-8). Medication adherence was graded as high (zero score), medium (1-2 score) and low (3-8 score). Results: A total of 193 hypertensive adults fulfilling the inclusion criteria were included. Low medication adherence was observed in 56 (29.01%) of the study participants. Majority (67.88%), had medium adherence, while a very low percentage (3.11%) had high medication adherence, as per the MMAS-8. Low adherence was found to be higher among participants belonging to low socio-economic status (39.44%) when compared to other classes. This association was statistically significant (p=0.0025). Those having diabetes had higher rates of poor adherence (66.67%) when compared to non-diabetics (13.24%), which was statistically significant (p<0.0001). Consuming ≥3 medications was another factor found to be significantly associated with low medication adherence (p<0.0001). Conclusions: We conclude that 29.01% of the study participants had low medication adherence. Low socio-economic status (Class IV+V), presence of diabetes mellitus and number of medications were the factors found to be significantly associated with low medication adherence.